Characterization of a Bacterial Symbiont Asaia sp. in the White-Backed Planthopper, Sogatella furcifera, and Its Effects on Host Fitness - Li, Fei; Hua, Hongxia; Ali, Asad; Hou, Maolin (Frontiers in Microbiology, 2019)
The white-backed planthopper (WBPH), Sogatella furcifera Horváth (Hemiptera: Delphacidae), is an economically significant rice insect pest that harbors a primary fungal yeast-like symbiont (YLS), and some secondary bacterial symbionts like Wolbachia and Cardinium. In the present study, an additional bacterial symbiont in WBPH was characterized. Phylogenetic analysis employing the 16S rRNA gene showed a bacterium closely related to Asaia of Nilaparvata lugens and Nysius expressus, and Asaia krungthepensis. TEM observation of the bacterium showed the typical morphology of Asaia sp. with signature filamentous structures in the nucleoid region. These results indicate that the bacterium belongs to Asaia. The Asaia bacterium was detected in all the tested individual adults and tissues of the laboratory WBPH population but showed varying infection rates (ca 45%) in the field collected WBPH populations. Quantitative PCR analysis revealed that Asaia sp. were significantly more abundant in WBPH females than males, and mainly distributed in the guts, fatty bodies, and salivary glands. Asaia-infected WBPH were of shorter nymphal duration and heavier adult weight than Asaia-free WBPH, while Asaia-free WBPH comparatively fed more, indicating that Asaia plays a role in improving WBPH fitness through involvement in host’s nutrient supply.